2019
DOI: 10.1111/desc.12875
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual assessment of early child development: Analyses from repeated observations of children in Kenya

Abstract: In many low‐ and middle‐income countries, young children learn a mother tongue or indigenous language at home before entering the formal education system where they will need to understand and speak a country's official language(s). Thus, assessments of children before school age, conducted in a nation's official language, may not fully reflect a child's development, underscoring the importance of test translation and adaptation. To examine differences in vocabulary development by language of assessment, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(77 reference statements)
1
8
0
Order By: Relevance
“…Challenges such as translations influencing sensitivity (Knauer, Karinger, Jakiela, Ozia, & Fernald, 2019 ), bias and limited comparison to norms (Weber, Fernald, Galasso, & Ratsifandrihamanana, 2015 ) experienced in test adaptations justify the need to develop local tests especially for isiZulu, the most widely spoken South African language. The aim of our study was to develop a one-word receptive vocabulary test appropriate for screening and diagnosis of isiZulu-speaking preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges such as translations influencing sensitivity (Knauer, Karinger, Jakiela, Ozia, & Fernald, 2019 ), bias and limited comparison to norms (Weber, Fernald, Galasso, & Ratsifandrihamanana, 2015 ) experienced in test adaptations justify the need to develop local tests especially for isiZulu, the most widely spoken South African language. The aim of our study was to develop a one-word receptive vocabulary test appropriate for screening and diagnosis of isiZulu-speaking preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while multilingual vocabulary assessment is contextually appropriate, the results do not necessarily reflect whether a child has developed adequate vocabulary in each individual language to support reading. Knauer et al (2019) also developed a multilingual productive vocabulary test. They found that baseline performance on their test predicted receptive vocabulary in English, Kiswahili, and Luo, and multilingual productive vocabulary measured five weeks later.…”
Section: Vocabulary Research In Sub-saharan Africamentioning
confidence: 99%
“…Numerous studies included in this issue present adaptation and/ or testing of behavioral and neuroimaging measures to ensure that these are locally appropriate, feasible, and acceptable for measurement of children's behavioral (Milosavljevic et al, ; Obradović et al, ; Willoughby, Piper, Oyanga, & Merseth, ), language (Dulay, Cheung, & McBride, ; Jasińska, Wolf, Jukes, & Dubeck, ; Knauer, Kariger, Jakiela, Ozier, & Fernald, ; Lervåg, Dolean, Tincas, & Melby‐Lervåg, ), and neural development (Lloyd‐Fox et al, ; Perdue et al, ; Pyykkö et al, ; Turesky et al, ; Wijeakumar, Kumar, M. Delgado Reyes, Tiwari, & Spencer, ). Milosavljevic et al (), for example, test the adaptation of the Mullen Scales of Early Learning in the Gambia and cast light on developmental patterns in children aged 5–24 months.…”
Section: Introduction To Special Issue On Global Child Development Stmentioning
confidence: 99%
“…Increased attention to biological embedding of early experience, children's emotional outcomes, and longitudinal investigation of developmental changes are positive and welcome trends in global child research. Knauer et al () assess interrelations between language skills across languages in multilingual children in Kenya.…”
Section: Introduction To Special Issue On Global Child Development Stmentioning
confidence: 99%
See 1 more Smart Citation